Synthesis of alpha-tetrasubstituted triazoles by copper-catalyzed silyl deprotection/azide cycloaddition - Palchak, Zachary L.; Nguyen, Paula T.; Larsen, Catharine H. (Beilstein Journal of Organic Chemistry, 2015)
Propargylamines are popular substrates for triazole formation, but tetrasubstituted variants have required multistep syntheses involving stoichiometric amounts of metal. A recent cyclohexanone–amine–silylacetylene coupling forms silyl-protected tetrasubstituted propargylamines in a single copper-catalyzed step. The development of the tandem silyl deprotection–triazole formation reported herein offers rapid access to alpha-tetrasubstituted triazoles. A streamlined two-step approach to this uncommon class of hindered triazoles will accelerate exploration of their therapeutic potential. The superior activity of copper(II) triflate in the formation of triazoles from sensitive alkyne substrates extends to simple terminal alkynes.
Keywords: azide; copper catalysis; multicomponent reactions; tetrasubstituted carbon; triazole

(untitled) - Meldal, M.; Tornøe, C. W. (Chem. Rev., 2008)

(untitled) - Hein, J. E.; Fokin, V. V. (Chem. Soc. Rev., 2010)

(untitled) - Tornøe, C. W.; Christensen, C.; Meldal, M. (J. Org. Chem., 2002)

(untitled) - Rostovtsev, V. V.; Green, L. G.; Fokin, V. V.; Sharpless, K. B. (Angew. Chem., Int. Ed., 2002)

(untitled) - Brik, A.; Muldoon, J.; Lin, Y.-C.; Elder, J. H.; Goodsell, D. S.; Olson, A. J.; Fokin, V. V.; Sharpless, K. B.; Wong, C.-H. (ChemBioChem, 2003)

(untitled) - Brak, K.; Doyle, P. S.; McKerrow, J. H.; Ellman, J. A. (J. Am. Chem. Soc., 2008)

(untitled) - Patterson, A. W.; Wood, W. J. L.; Hornsby, M.; Lesley, S.; Spraggon, G.; Ellman, J. A. (J. Med. Chem., 2006)

(untitled) - Wood, W. J. L.; Patterson, A. W.; Tsuruoka, H.; Jain, R. K.; Ellman, J. A. (J. Am. Chem. Soc., 2005)

(untitled) - Zhang, L.; Chen, X.; Xue, P.; Sun, H. H. Y.; Williams, I. D.; Sharpless, K. B.; Fokin, V. V.; Jia, G. (J. Am. Chem. Soc., 2005)

(untitled) - Pagliai, F.; Pirali, T.; Del Grosso, E.; Di Brisco, R.; Tron, G. C.; Sorba, G.; Genazzani, A. A. (J. Med. Chem., 2006)

(untitled) - Srinivasan, R.; Uttamchandani, M.; Yao, S. Q. (Org. Lett., 2006)

(untitled) - Tron, G. C.; Pirali, T.; Billington, R. A.; Canonico, P. L.; Sorba, G.; Genazzani, A. A. (Med. Res. Rev., 2008)

(untitled) - Huisgen, R. (Pure Appl. Chem., 1989)

(untitled) - Gupte, A.; Boshoff, H. I.; Wilson, D. J.; Neres, J.; Labello, N. P.; Somu, R. V.; Xing, C.; Barry, C. E., III; Aldrich, C. C. (J. Med. Chem., 2008)

(untitled) - Ferreira, S. B.; Sodero, A. C. R.; Cardoso, M. F. C.; Lima, E. S.; Kaiser, C. R.; Silva, F. P., Jr; Ferreira, V. F. (J. Med. Chem., 2010)

(untitled) - Van Poecke, S.; Negri, A.; Gago, F.; Van Daele, I.; Solaroli, N.; Karlsson, A.; Balzarini, J.; Van Calenbergh, S. (J. Med. Chem., 2010)

(untitled) - Li, Y.; Shen, M.; Zhang, Z.; Luo, J.; Pan, X.; Lu, X.; Long, H.; Wen, D.; Zhang, F.; Leng, F.; Li, Y.; Tu, Z.; et al. (J. Med. Chem., 2012)

(untitled) - Testa, C.; Scrima, M.; Grimaldi, M.; D’Ursi, A. M.; Dirain, M. L.; Lubin-Germain, N.; Singh, A.; Haskell-Luevano, C.; Chorev, M.; Rovero, P.; Papini, A. M. (J. Med. Chem., 2014)

(untitled) - Brik, A.; Muldoon, J.; Lin, Y.-C.; Elder, J. H.; Goodsell, D. S.; Olson, A. J.; Fokin, V. V.; Sharpless, K. B.; Wong, C.-H. (ChemBioChem, 2003)

(untitled) - Blay, G.; Monleon, A.; Pedro, J. R. (Curr. Org. Chem., 2009)

(untitled) - Yoo, W. J.; Zhao, L.; Li, C.-J. (Aldrichimica Acta, 2011)

(untitled) - Pereshivko, O. P.; Peshkov, V. A.; Van der Eycken, E. V. (Org. Lett., 2010)

(untitled) - Cheng, M.; Zhang, Q.; Hu, X.-Y.; Li, B.-G.; Ji, J.-X.; Chan, A. S. C. (Adv. Synth. Catal., 2011)

(untitled) - Pierce, C. J.; Larsen, C. H. (Green Chem., 2012)

(untitled) - Palchak, Z. L.; Lussier, D. J.; Pierce, C. J.; Larsen, C. H. (Green Chem., 2015)

(untitled) - Pierce, C. J.; Nguyen, M.; Larsen, C. H. (Angew. Chem., Int. Ed., 2012)

(untitled) - Ma, X.; Gang, D. R. (Nat. Prod. Rep., 2004)

(untitled) - Clayden, J.; Donnard, M.; Lefranc, J.; Tetlow, D. J. (Chem. Commun., 2011)

(untitled) - Vardanyan, R. S.; Hruby, V. J. (Future Med. Chem., 2014)

(untitled) - Aucagne, V.; Leigh, D. A. (Org. Lett., 2006)

(untitled) - Fletcher, J. T.; Bumgarner, B. J.; Engels, N. D.; Skoglund, D. A. (Organometallics, 2008)

(untitled) - Fletcher, J. T.; Walz, S. E.; Keeney, M. E. (Tetrahedron Lett., 2008)

(untitled) - Beltrán, E.; Serrano, J. L.; Sierra, T.; Giménez, R. (Org. Lett., 2010)

(untitled) - Escamilla, I. V.; Ramos, L. F. R.; Escalera, J. S.; Hernandez, A. A. (J. Mex. Chem. Soc., 2011)

(untitled) - Heuft, M. A.; Collins, S. K.; Yap, G. P. A.; Fallis, A. G. (Org. Lett., 2001)

(untitled) - Meyet, C. E.; Pierce, C. J.; Larsen, C. H. (Org. Lett., 2012)

(untitled) - Jessop, P. G. (Green Chem., 2011)

(untitled) - Koradin, C.; Polborn, K.; Knochel, P. (Angew. Chem., Int. Ed., 2002)

(untitled) - Shinde, S. S.; Chi, H. M.; Lee, B. S.; Chi, D. Y. (Tetrahedron Lett., 2009)

(untitled) - Asano, K.; Matsubara, S. (Org. Lett., 2010)

(untitled) - Rossy, C.; Majimel, J.; Delapierre, M. T.; Fouquet, E.; Felpin, F.-X. (J. Organomet. Chem., 2014)